Effects of municipal solid waste compost and fertilizers on the biomass production and yield of BRRI dhan 50 (Progressive Agriculture, 2018)
An experiment was conducted at the soil science field laboratory of Bangladesh Agricultural University(BAU), Mymensingh during Boro season of 2011 to evaluate the effect of municipal waste compost (MSW) and chemical fertilizer on the biomass production and yield of boro rice(BRRI dhan50). The experimental field was silty loam in texture having pH 6.58, organic carbon 1.0% total nitrogen 0.17%, availableP11.0ppm, exchangeable K 0.11meq/100 gm soil and available sulphur 11.8ppm. the experiment comprised of 9 treatments T0 = Control (no fertilizer or compost), T1= 100% recommended fertilizer dose (N, P, K, S), T2 = Compost 5 t ha-1, T3= Compost 5 t ha-1 +100% RDF, T4 = Compost 7.5 t ha-1, T5 = Compost 7.5 t ha-1+100% RDF, T6 =Compost 10 t ha-1,  T7= Compost 10 t ha-1 +100% RDF,  T8= Compost 20 t ha-1.Compost was prepared  with MSW collected from Mymensingh. Recommended dose of NPK and S at 135, 20, 50 and 10 kg/ha respectively were applied as Urea, TSP, MOP and Gypsum. Application of MSW compost either alone or in combination of fertilizer at positive and significant effect on all the parameter studied. The plant characters like plant height, panicle length, effective tillers per hill, grain per panicle, Shoot dry weight, Root dry weight were significantly influenced by the different treatments. The highest biomass yield of 925 g/m2 was recorded with the  T7 treatment and the lowest yield was noted in the T0 treatment. The same treatment i.e. T7 demonstrated the highest grain yield (6.3t/ha) and the T0 (control) treatment had the lowest yield (3.90 t/ha). Application of MSW compost@ 10 ton/ha with 100% RDF (T7) also produced the highest straw yield. Lone application of MSW compost even at 20 ton/ha was not comparable with recommended dose of fertilizer in producing rice yield. Further study in needed to explore a positively to reduce fertilizer dose to the use of MSW for achieving sustainable soil fertility and crop yield.Progressive Agriculture 29 (2): 82-90, 2018